2016
DOI: 10.3109/14756366.2016.1163342
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, cytotoxic, anti-lipoxygenase and anti-acetylcholinesterase capacities of novel derivatives from harmine

Abstract: We synthesized two series of new hydrazide harmine derivatives. The reaction of harmine 1 with ethyl acetate chloride afforded the corresponding ethyl ester 2. The treatment of 2 with hydrazine hydrate gave the hydrazide 3 which further converted into hydrazones 4a-j and dihydrazides 5a-c. A series of new triazoles 7a-f has also been prepared from the suitable propargyl harmine 6. The synthesized derivatives were characterized by 1 H-NMR, 13 C-NMR, and HRMS and evaluated for their activities against MCF7, HCT1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Twenty novel hybrid compounds comprising two distinct pharmacophores-harmine/ β-carboline and coumarin, connected via triazole linker-were synthesized using CuAAC from harmine-based azides and coumarin alkynes (4 and 5) and coumarin azides and harmine-based alkynes (11)(12)(13), respectively. The evaluation of their antiproliferative activity in vitro against a panel of human cell lines revealed that seven harmirins display activities in the single-digit micromolar range against MCF-7 and HCT116.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty novel hybrid compounds comprising two distinct pharmacophores-harmine/ β-carboline and coumarin, connected via triazole linker-were synthesized using CuAAC from harmine-based azides and coumarin alkynes (4 and 5) and coumarin azides and harmine-based alkynes (11)(12)(13), respectively. The evaluation of their antiproliferative activity in vitro against a panel of human cell lines revealed that seven harmirins display activities in the single-digit micromolar range against MCF-7 and HCT116.…”
Section: Discussionmentioning
confidence: 99%
“…In general, β-carbolines possess a wide range of biological activities, such as anticancer, anti-inflammatory, antiviral, antiparasitic, hallucinogenic, etc. [3,5,[10][11][12][13]. Today, the abundance of research in this field focuses on their anticancer properties.…”
Section: Introductionmentioning
confidence: 99%
“…(7‐Methoxy‐1‐methyl‐β‐carbolin‐9‐yl)acetic acid ethyl ester (10) : Using ethyl 2‐chloroacetate as the alkylating agent, we obtained 10 (338 mg, 1.13 mmol, 80 %) as an off‐white solid. 1 H NMR (500 MHz, [D 6 ]DMSO): δ =1.22 (t, J= 7.0 Hz, 3 H), 2.82 (s, 1 H), 3.88 (s, 1 H), 4.20 (q, J= 7.0 Hz, 2 H), 5.51 (s, 2 H), 6.89 (dd, J= 1.8, 8.6 Hz, 1 H), 7.28 (d, J= 1.8 Hz, 1 H), 7.88 (d, J= 5.2 Hz, 1 H), 8.09 (d, J= 8.6 Hz, 1 H), 8.18 ppm (d, J= 5.2 Hz, 1 H); 13 C NMR (125 MHz, [D 6 ]DMSO): δ =14.4, 22.8, 46.7, 56.1, 61.6, 94.2, 110.0, 112.7, 114.6, 122.7, 129.1, 135.4, 138.8, 141.0, 143.8, 161.1, 170.0 ppm; HRMS: m / z : calcd for C 17 H 18 N 2 O 3 +H + : 299.1395 [ M +H] + ; found: 299.1391 (Δ f =0.33 ppm).…”
Section: Methodsmentioning
confidence: 99%
“…If isoxazoline derivatives were associated with a 10-fold drop of inhibition potency (IC 50 = 11 μM for the most active analogue 12), 12 a large series of triazoles and hydrazides were found completely inactive against AChE (IC 50 > 100 μM). 13 Natural βcarbolines bearing a 9-methoxy group were also marginally active. 23 Globally, the functionalization of positions 1 and 7 only provided a limited impact (e.g., IC 50 > 10 μM for 1, 9a, and 9b).…”
Section: ■ Acetyl-and Butyrylcholinesterase (Ache/buche) Inhibitorsmentioning
confidence: 96%